2021
DOI: 10.3389/fevo.2021.669352
|View full text |Cite
|
Sign up to set email alerts
|

Specialized Metabolites in Floral Resources: Effects and Detection in Buff-Tailed Bumblebees

Abstract: The selection of appropriate food resources by bees is a critical aspect for the maintenance of their populations, especially in the current context of global change and pollinator decline. Wild bees have a sophisticated ability to forage selectively on specific resources, and can assess the quality of pollen using contact chemosensory perception (taste). While numerous studies have investigated the detection of pollen macronutrients in bees and their impact on bee health and reproductive success, only a few s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 134 publications
1
6
0
Order By: Relevance
“…For this reason, it is likely that nectar palatability is largely determined by the sensilla on the proboscis. Based on our current results and those of previous studies (Sculfort et al, 2021; Tiedeken et al, 2014), we predict that bumblebees have a limited ability to detect naturally-occurring concentrations of toxic or bitter compounds in nectar. Future studies that survey a greater variety of compounds will be necessary to confirm this.…”
Section: Discussionsupporting
confidence: 65%
“…For this reason, it is likely that nectar palatability is largely determined by the sensilla on the proboscis. Based on our current results and those of previous studies (Sculfort et al, 2021; Tiedeken et al, 2014), we predict that bumblebees have a limited ability to detect naturally-occurring concentrations of toxic or bitter compounds in nectar. Future studies that survey a greater variety of compounds will be necessary to confirm this.…”
Section: Discussionsupporting
confidence: 65%
“…It will be important to test the fitness implications of this variance in floral resource quality for pollinating insects, especially as their preferences do not always increase their fitness ( Hoover et al, 2012 ). Our study did not evaluate other components of pollen and nectar, such as bacteria, sterols, plant secondary metabolites, and micro-nutrients, but they have shown to be important drivers of both flower-visiting insect behaviour and fitness ( Palmer-Young et al, 2018 ; Vannette, 2020 ; Sculfort et al, 2021 ; Filipiak et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Knauer and Schiestl ( 2017 ) found that B. napa plants that had increased levels of the glucosinolate Glucobrassicanapin caused by foliar herbivory tended to have reduced visitation by bumblebees, but this effect could also have been related to indirect effects such as delayed flowering or a change in volatile organic compounds (discussed below). To our knowledge, the only available test whether glucosinolates have a direct effect on foraging preference of bees was conducted by testing consumption of sugar solutions containing different concentrations of the glucosinolates Scopolamine, Amygdalin and Sinigrin by bumblebees (Sculfort et al 2021 ). However, results were difficult to interpret, because both high and low but not intermediate concentrations of Amygdalin and Sinigrin repelled bees, whereas Scopolamine only had attractant effects (Sculfort et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, the only available test whether glucosinolates have a direct effect on foraging preference of bees was conducted by testing consumption of sugar solutions containing different concentrations of the glucosinolates Scopolamine, Amygdalin and Sinigrin by bumblebees (Sculfort et al 2021 ). However, results were difficult to interpret, because both high and low but not intermediate concentrations of Amygdalin and Sinigrin repelled bees, whereas Scopolamine only had attractant effects (Sculfort et al 2021 ). In addition we cannot exclude that additonal plant parameters not measured by us could be the causative agent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation